The Role of Customer Experience in Sustaining Open Banking Usage: A Bibliometric Review - Mappanessa, Marwah; Widuri, Rindang (Borong Newinera Publisher, 2025)
Open banking has emerged as a cornerstone of digital financial transformation, bridging technological innovation with the needs of modern customers. This study explores key topics such as service quality, privacy, and security, which are critical factors in fostering customer satisfaction and loyalty. The findings reveal that technologies like blockchain and open APIs play a vital role in enhancing transparency and trust, while omnichannel strategies personalize user experiences. However, there are gaps in understanding the long-term relationship between privacy, security, and service quality, particularly in developing markets. This research provides practical insights for organizations to prioritize innovations that enhance customer experience and data protection. By expanding the scope of future studies and integrating multidisciplinary approaches, this study aims to lay the foundation for a more inclusive, secure, and sustainable open banking ecosystem.